Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Văn học, 2004)
Nguyễn Minh Châu; Lý Biên Cương; Nguyễn Địch Dũng; Trần Dũng; Anh Đức; Trần Đăng; Nguyễn Phan Hách; Vũ Hạnh.